Burn conversion possibly caused by COVID-19 infection: A case report - Dongkyung Seo; Taku Maeda; Yuhei Yamamoto; Emi Funayama; Takahiro Miura; Norifumi Matsuda; Kosuke Ishikawa (Elsevier, 2024)
We report a case in which burn wound conversion occurred in a patient with concomitant COVID-19 pneumonia. To our knowledge, this is the first report to present sequential clinical photographs in a case of burn with COVID-19. Abundant oxygenation with huge head room, massive fluid resuscitation, and anticoagulation therapy may be required in COVID-19 patients even with a narrower surface of burn.